QUANTITATIVE ANALYSIS OF GLUCOSE LEVEL IN BLOOD SERUM OF THREE GOAT BREEDS (CAPRA HIRCUS) IN NORTHERN PAKISTAN - A. Khan a; H. Bibi a; M. Z. Khan b; S. Hydera; S. Shah c; F. Begum b; M. T. Hafeeza; A. Rehman a (Journal of Animal and Plant Sciences, 2020)
Glucose is used as fuel for energy production, leading to maintaining physiological phenomena of cell and animal body. The blood glucose level in ruminants is actively transported through bloodstreams and circulating carbohydrates. The study aimed to evaluate the glucose level as an indicator of energy in goat breeds (Koh-e-Ghizer, Gojali and Baltistani) inhabiting three regions of Gilgit-Baltistan (GB), namely Ghizer, Baltistan and Hunza-Nagar. Data were collected from both male and female goats with the age of two years and above, determined based on teeth composition. Samples of blood were randomly taken from 270 goats (120 male &150 females) by using 5ml clinical syringes and serum was obtained by centrifugation process. The quantity of glucose in mg/dl of serum was determined by analyzing the serum in Micro-lab 300. These goats majorly feed on pure organic forage in high altitude pastures in all three regions. The results revealed that the average level of glucose obtained from male goats was 65.50±16.77 mg/dl in Ghizer, 76.40±16.11 mg/dl in Baltistan, 87.95±11.52 mg/dl in Hunza-Nagar and glucose level in female was 67.94±15.02 mg/dl in Ghizer, 70.92±15.01mg/dl in Baltistan, and 83.82±9.51 mg/dl in Hunza Nagar respectively. The analysis of variance (ANOVA) has shown significant differences of glucose within sex and region at p≤0.001. Serum glucose was observed higher in female goats in comparison with male goats in district Ghizer. It also reflects the pastures’ potential in the three major regions of Gilgit-Baltistan, need to be noticed by the herders and livestock department in the regions while taking initiatives for pasture management.
Keywords: Goats; serum glucose; Gilgit-Baltistan; pastures potential